A Systematic Literature Review on the Role of Google Sites Digital Platform in Strengthening Learning Evaluation and Reflection - Ida Ayu Intan Nandini; Ketut Agustini; I Gde Wawan Sudatha (Cetta: Jurnal Ilmu Pendidikan, 2026)
The development of digital technology has initiated significant transformations in educational practices, requiring the adaptation of learning methods in line with the demands of the 21st century. Google Sites has emerged as a digital portfolio platform with the potential to encourage students' metacognitive reflection skills. However, in-depth exploration of its pedagogical use, particularly in the context of Indonesian secondary schools with various infrastructure challenges, is still limited. This study aims to structurally identify the challenges and advantages of Google Sites in enhancing metacognitive thinking and to formulate a conceptual model for facilitating reflective learning. The method used is a Systematic Literature Review (SLR) with the PRISMA protocol, analysing 13 selected articles from the Web of Science, Google Scholar, and Garuda databases. The results of the study show that Google Sites is effective in acting as metacognitive scaffolding, accelerating the feedback cycle for authentic assessment, and expanding the Zone of Proximal Development through transparent collaboration between students, teachers, and parents. Its effectiveness is the result of the dynamic interaction between the context of application, pedagogical design, and infrastructure readiness. The study concludes that Google Sites can be a digital learning model in line with the principles of the Merdeka Curriculum, namely creating a reflective, adaptive, participatory, and sustainable learning ecosystem.